TARIAN SARA RE SELO (TARIAN PERANG) SUKU WAYOLI KABUPATEN HALMAHERA BARAT - Hasim, Rustam (Jurnal GeoCivic, 2024)
Sara re Selo dance is a war dance originating from the Wayoli Tribe in West Halmahera Regency. This dance has existed since the Portuguese to Dutch colonial era. For the Wayoli Tribe, the Sara re Selo dance is interpreted as a form of appreciation and respect for their ancestors who fought to expel the invaders. As a war dance, it can be seen from the movements and expressions of the dancers when dancing the Sara re Selo dance. The Sara re Selo dance depicts the struggle of the Wayoli Tribe in defending the truth, dignity and honor of the community. Therefore, this dance is often considered a symbol of the heroism and courage of the Wayoli Tribe.The method used in this study is descriptive qualitative which is focused on examining the implementation of the Sara re Selo dance of the Wayoli Tribe in West Halmahera Regency. The data collected in this study are; Field research was conducted by means of interviews, observations, documents, and Focused Group Discussions (FGD).This study concludes that the Sara re Selo dance is an interesting performance that is performed during the Wayoli Tribe's traditional thanksgiving, picking up guests, traditional performances to welcome the leader of the Tribe Chief when arriving at the Village which is held in (Batangan ma Adu) Wala Sasadu meaning Traditional House. The Sara re Selo dance has a very deep meaning besides maintaining the balance of growth and soul, it also teaches about cooperation between men and women in gender equality.